2020
DOI: 10.1177/1756284820954114
|View full text |Cite
|
Sign up to set email alerts
|

Model-based evaluation of the cost effectiveness of 3 versus 6 months’ adjuvant chemotherapy in high-risk stage II colon cancer patients

Abstract: Background: Our aim was to evaluate the cost effectiveness of 3 months’ adjuvant chemotherapy versus 6 months in high-risk (T4 stage + microsatellite stable) stage II colon cancer (CC) patients. Methods: Using the validated PATTERN Markov cohort model, which simulates the disease progression of stage II CC patients from diagnosis to death, we first evaluated a reference strategy in which high-risk patients were treated with chemotherapy for 6 months. In the second strategy, treatment duration was shortened to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…1 ). The remaining 65 studies underwent full text review, with 38 meeting the inclusion criteria [ 4 6 , 18 – 52 ]. Reasons for exclusion during the full text review included studies being reviews or commentaries, pertaining to rectal cancer or neoadjuvant therapies, not being economic evaluations or full text being unavailable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). The remaining 65 studies underwent full text review, with 38 meeting the inclusion criteria [ 4 6 , 18 – 52 ]. Reasons for exclusion during the full text review included studies being reviews or commentaries, pertaining to rectal cancer or neoadjuvant therapies, not being economic evaluations or full text being unavailable.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were modelled on data from the SCOT trial, a randomised controlled trial of 3 versus 6 months of oxaliplatin-based doublet AC in a cohort of high-risk stage II and stage III patients [ 4 , 6 , 47 , 48 ]. Two of these studies concluded that 3 months of AC dominates 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 3.8 Three vs. six month duration Three studies were modelled on data from the SCOT trial, a randomised controlled trial of 3 versus 6 months of oxaliplatin-based doublet AC in a cohort of high-risk stage II and stage III patients. [44][45][46][47] Two of these studies concluded that 3 months of AC dominates 6 months. The remaining study assumed partial prescription of shortened AC duration based on a survey of physicians (stage II: 18%; stage III: 50%) but despite this limited uptake, a 3-month treatment duration was still cost-effective.…”
Section: Oxaliplatin-based Acmentioning
confidence: 99%
“…47 Jongeneel et al analysed AC in high-risk stage II patients by speci c regimen, concluding that 3 months of CAPOX dominates 6 months but that 3 months of FOLFOX was not cost-effective. 44 Importantly, they considered T4 staging and microsatellite stability (MSS) as high-risk histological features compared to the more expansive de nition of high risk disease utilised in the SCOT trial. 14 3.9 Biomarker vs. SOC To et al modelled the use of post-operative circulating tumour DNA (ctDNA) in unselected stage II CRC patients.…”
Section: Oxaliplatin-based Acmentioning
confidence: 99%